A novel wide bandwidth FBSSIR integrated low noise amplifier for satellite navigational receiver system. (November 2021) - Vignesh, R.; Gorre, Pradeep; Kumar, Sandeep
Abstract: This paper presents a Folded Butterfly Stub Stepped Impedance Resonator (FBSSIR) integrated low noise amplifier (LNA) implemented using packaging technology for the satellite navigation receiver system. By employing a novel structural deformation of a stepped-impedance-resonator (SIR), the proposed FBSSIR is achieved with a more compact structure, controllable transmission zero, adjustable center frequency, and adjustable bandwidth. The designed FBSSIR acts as a filter, and the input-output matching network is integrated into the proposed core LNA circuit. The Design-of-experiment (DoE) analysis is performed to analyze the passive component's sensitivity becoming desensitized, while statistical analysis is presented for the proposed FBSSIR integrated LNA to predict the percentage error tolerance. Its measurement result provides gain above 22 dB in the wide bandwidth from 1.6 GHz to 2.5 GHz, minimum NF of 2.7 dB at 1.8 GHz, which varies from 3 dB to 4.5 dB. The calculated area of FBSSIR integrated LNA is 10.7 × 2 cm 2, while LNA is 3.3 × 1.6 cm 2 . It exhibits an input and output 1-dB compression point (IP1dB & OP1dB ) of −23dBm and +2.3dBm.